Effects of Ban Xia Xie Xin Decoction on GERD of Cold and Heat in Complexity Syndrome - Tandean, Erick Okto; Sumantri, Twinky Zebrina Cysta; He, Ling; Amalia, Anindini Winda (Buletin Farmatera, 2026)
Abstract: Gastroesophageal Reflux Disease (GERD) presents significant diagnostic challenges and diminishes quality of life. This study evaluates the efficacy of Ban Xia Xie Xin Decoction on patients with GERD exhibiting "Cold and Heat in Complexity Syndrome." A one-group pretest-posttest design was conducted at the Jiangxi University of Chinese Medicine Affiliated Hospital from January to February 2025. This research aims to study the effects of Ban Xia Xie Xin Decoction on GERD of cold and heat in complexity syndrome. Ten respondents were selected via purposive sampling based on strict inclusion criteria. Data normality was assessed using the Shapiro-Wilk test, while treatment effects were analyzed using the Wilcoxon signed-rank test (α=0.05). Primary outcomes were measured using the Reflux Disease Questionnaire (RDQ) and Chinese Medicine Evaluation Report (CMER) scores. Statistical analysis revealed a significant decrease in symptom severity (α = 0.005 0.01), leading to the rejection of the null hypothesis. Post-intervention mean scores decreased by 18.70 for RDQ and 13.00 for CMER, indicating a substantial reduction in acid reflux and epigastric pain. Ban Xia Xie Xin Decoction significantly alleviates symptoms in GERD patients with Cold and Heat in Complexity Syndrome. These findings support the integration of traditional decoctions in managing chronic gastrointestinal disorders.